2018
DOI: 10.3153/fh18008
|View full text |Cite
|
Sign up to set email alerts
|

Ft-Ir Spectroscopy Characterization and Chemometric Evaluation of Legumes Extracted With Different Solvents

Abstract: In this study, FT-IR spectroscopy was applied for rapid characterization and discrimination of commonly consumed legumes extracted by different solvents in combination with principal component analysis (PCA) for the first time. Dried soy bean, white bean, chickpea, red lentil, and pinto bean were extracted by water (W), ethanol (E), acetone/water (AW) and acetone/water/acetic acid (AA). The effect of each solvent on different legume extracts was demonstrated by identifying the functional groups using FT-IR spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…In addition, to interpret data obtained from analysis were closer to the potential real food process applications. The previous study conducted our group has also reported that water extraction of chickpea samples yielded more total phenolic content than the samples extracted by ethanol, acetone, and acidified acetone (Dıblan et al, 2018). In that study, it was seen that Folic-Ciocalteu method measured more phenolic contents in water extracts of legumes than organic extracts since the water soluble proteins made contribution to the results due to their amino acid residues containing aromatic ring.…”
Section: Functional Properties Of Chickpea Cultivarsmentioning
confidence: 80%
See 1 more Smart Citation
“…In addition, to interpret data obtained from analysis were closer to the potential real food process applications. The previous study conducted our group has also reported that water extraction of chickpea samples yielded more total phenolic content than the samples extracted by ethanol, acetone, and acidified acetone (Dıblan et al, 2018). In that study, it was seen that Folic-Ciocalteu method measured more phenolic contents in water extracts of legumes than organic extracts since the water soluble proteins made contribution to the results due to their amino acid residues containing aromatic ring.…”
Section: Functional Properties Of Chickpea Cultivarsmentioning
confidence: 80%
“…Because the functional property values of chickpea extracts were similar to each other and between these values significant differences mostly did not observed. Dıblan et al, (2018) investigated the effects of different solvents on TPC of chickpea extracts and reported that water extraction provided the highest phenolic content (1829 ±12 μg GAE/g that was similar to our findings) than ethanol (1478 ±79 μg GAE/g), acetone (875 ±21 μg GAE/g) and acidified acetone (729 ±24 μg GAE/g) extraction methods (Dıblan et al, 2018). Arab, Helmy, and Bareh (2010) measured the WBC and OBC of chickpea flours to be used in functional pasta production and determined the similar OBC values but lower WBC values than our findings (Arab et al, 2010).…”
Section: Functional Properties Of Chickpea Cultivarsmentioning
confidence: 99%
“…The stretching band of carbonyl (CO) groups appeared around 1730 cm –1 , as well as aromatic skeleton vibrations around 1590 cm –1 and clear evidence of phenolic moieties at 1450, 1370, 1270, and 1040 cm –1 . Bands associated to OH vibrations in primary and secondary alcohols appeared at 1150 and 1040 cm –1 , being originated by carbohydrates and indicating certain contamination due to polysaccharides. , …”
Section: Resultsmentioning
confidence: 99%
“…These results were in accordance with the fat contents found in the proximate analysis of the flours. Moreover, Amide I (~1600 cm −1 ), Amide II (~1500 cm −1 ), and Amide A (~3300 cm −1 ) bands, where C═O, CN, and NH stretching modes of proteins are observed, can be easily detected from the FTIR spectrum (Demir et al, 2015; Dıblan et al, 2018; Guerrero et al, 2013). Overall, these peaks provide information regarding the polysaccharides, fat, and protein in the flours.…”
Section: Resultsmentioning
confidence: 99%